(untitled) (International relations and international law Journal, 2019)
In this study, we conducted a review of literature of instruments to measure intercultural competence in the domain of education and we evaluated the most relevant and scientifically valid to teachers. Eight instruments were identified and the Multiculturally Efficacy Scale was select. The purpose was to apply this instrument to analyse intercultural competence of 88 teachers from primary schools of the International School of Geneva. A comparison between English-speaking teachers and the French-speaking teachers about experiences with diversity, multicultural competence and the conception of multiculturalism in a multicultural school environment was also verified. Preliminary analyses comparing two groups revealed some difference but both groups of teachers have an attitude regarding diversity.We would discuss the results concerning this experience of diversity in English-speaking teachers and French-speaking. Findings lead to directions for future research. Key words: competence, cultural, intercultural, transcultural, cross-cultural, multicultural, scale, inventory, education, teacher training, teacher education.